2005
DOI: 10.1142/9789812569189_0008
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenesis and Vitellogenin Uptake into Oocytes

Abstract: The yolk proteins found in the oocyte of oviparous animals are synthesized by the liver as a large lipophosphoglycoprotein precursor, vitellogenin (Vtg), which represents a vital, sole source of nutrient for the developing larvae. Vitellogenesis underlies early development of oviparous animals. The Vtg gene is extremely sensitive to estrogen and other steroid hormones. Thus, vitellogenesis is a useful model for studying hormonal regulation of eukaryotic gene expression. The Oreochromis aureus vitellogenin, OaV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 99 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…PFOS has previously been suggested to be a weak ER ligand (Benninghoff et al, 2011;Cheng et al, 2010;Liu et al, 2007), but such a direct interaction may appear as a less plausible explanation when taking into consideration the long lag-time between PFOSexposure and transcriptional responses. Several factors besides E2 might also modulate expression of E2-regulated genes, including pituitary factors (Vaisius et al, 1991), other hormones or receptor cross-talks (Ding, 2005;Mori et al, 1998;Nuñez et al, 1997). Several nuclear receptors have been suggested to affect estrogenic gene expression.…”
Section: Effects Of Pfosmentioning
confidence: 99%
“…PFOS has previously been suggested to be a weak ER ligand (Benninghoff et al, 2011;Cheng et al, 2010;Liu et al, 2007), but such a direct interaction may appear as a less plausible explanation when taking into consideration the long lag-time between PFOSexposure and transcriptional responses. Several factors besides E2 might also modulate expression of E2-regulated genes, including pituitary factors (Vaisius et al, 1991), other hormones or receptor cross-talks (Ding, 2005;Mori et al, 1998;Nuñez et al, 1997). Several nuclear receptors have been suggested to affect estrogenic gene expression.…”
Section: Effects Of Pfosmentioning
confidence: 99%
“…Ding (2005) reported that Vtg has a MW between 200−700 kDa, similar to killifish, Fundulus heteroclitus (200 kDa). In mature female of teleost oviparous species, the Vtg is an essential nutrition source for oocyte and embryo development through vitellogenesis process (Lubzens et al, 2010;Ding, 2005). In the natural condition, the level of Vtg indicates the stage of gonad maturation in female species (Hara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In several species, Vtg has a molecular weight (MW) between 140−200 kDa (Komatsu & Hayashi, 1997). Ding (2005) reported that Vtg has a MW between 200−700 kDa, similar to killifish, Fundulus heteroclitus (200 kDa). In mature female of teleost oviparous species, the Vtg is an essential nutrition source for oocyte and embryo development through vitellogenesis process (Lubzens et al, 2010;Ding, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The VtG lipoproteins are the major yolk precursors; they are synthesized by hepatocytes, secreted into the general circulation and are taken up from the maternal circulation by developing oocytes. The hepatic vtg genes are highly responsive to oestrogen stimulation (Ding, 2005; Hiramatsu et al , 2006), and as oestrogen secretion increases during ovarian recrudescence into the vitellogenesis stage, so does plasma total Vtg concentration (Hiramatsu et al , 2006; Babin et al , 2007). By mid‐vitellogenesis, the plasma total Vtg fraction, which comprises a mixture of different Vtg lipoprotein species, is a major contributor to the total plasma lipoprotein concentration.…”
Section: Innate Body Defences Of Teleosts With An Emphasis On Embryosmentioning
confidence: 99%
“…This transfer presumably occurs at the apices of the extensions of the oocyte cytoplasm that traverse the ZP. Within the oocytes, the Vtgs are cleaved into lipovitellin (Lv) derivatives (Ding (2005), the spectrum of which is sensitive to the physiological status of the maternal brood stock (Gündel et al , 2007). The lipovitellin (Lv) derivatives of the Vtgs, together with lipids in the ooplasm, represent the major nutrients for the developing embryo.…”
Section: Innate Body Defences Of Teleosts With An Emphasis On Embryosmentioning
confidence: 99%